2021
DOI: 10.3390/ijerph18010307
|View full text |Cite
|
Sign up to set email alerts
|

The Related Risk Factors of Diabetic Retinopathy in Elderly Patients with Type 2 Diabetes Mellitus: A Hospital-Based Cohort Study in Taiwan

Abstract: Diabetic retinopathy (DR), caused by small vessel disease, is the main cause of blindness in persons with diabetes. Taiwan is one of the Asian countries with the highest prevalence rate of DR. The purpose was to investigate the related risk factors of DR in elderly patients with type 2 diabetes mellitus (T2DM), in Lee’s Endocrinology Clinic. 792 T2DM patients over 60 years old were invited to have an outpatient visit at least every three months, and all of them were asked to undergo a standardized interview an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…By reviewing the full text of the remaining 318 articles, 305 articles were excluded for various reasons. Finally, 13 cohort studies [ 8 , 11 , 13 , 19 28 ] including 7459 participants were considered relevant and included in the meta-analysis. The characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…By reviewing the full text of the remaining 318 articles, 305 articles were excluded for various reasons. Finally, 13 cohort studies [ 8 , 11 , 13 , 19 28 ] including 7459 participants were considered relevant and included in the meta-analysis. The characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus is a common, chronic metabolic disease that threatens human health. 1 One of the major complications of diabetes is diabetic cardiomyopathy (DCM), which causes patients to be prone to heart failure in the absence of other risk factors, such as hypertension and coronary artery disease. 2 Numerous molecular mechanisms have been proposed to explain the underlying pathophysiology of DCM, including impaired insulin signalling, excess fatty acid (FA) oxidation, reactive oxygen species (ROS) formation, abnormal autophagy, and mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a common, chronic metabolic disease that threatens human health 1 . One of the major complications of diabetes is diabetic cardiomyopathy (DCM), which causes patients to be prone to heart failure in the absence of other risk factors, such as hypertension and coronary artery disease 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The major consumption areas are in the Asia Pacific region, led by the Chinese mainland, Malaysia, and India [4]. In recent years, many studies have revealed that chewing too much areca nut increases the risk of oral cancer [5,6] and can impact the human cardiovascular, nervous, gastrointestinal, metabolic respiratory, and reproductive systems [7,8]. Therefore, food researchers and medical researchers increasingly focus on areca nuts.…”
Section: Introductionmentioning
confidence: 99%
“…It also has significant activity on the nervous system, digestive tract, and cardiovascular system. [7,8]. Arecaidine and guvacine can combine with γ-aminobutyric acid and GABA receptors to reflect the physiological effect of denervation, block GABA's nerve inhibition effect, and make those who chew it excitable and pleasant [10].…”
Section: Introductionmentioning
confidence: 99%